The Importance of Practical Focus in Increasing Motivation and Improving the Assistion of Educational Content in Medical Students - Kuchkarovich, Holbekov Bahodir (American Journal of Biology and Natural Sciences, 2024)
One of the unique features of teaching in medical universities is the absence of the method “Learn from mistakes ". Based on the psychological characteristics of students of higher medical educational institutions when studying fundamental and clinical sciences, taking into account the experience of leading foreign medical universities in the field of training students, as well as the modern practice of pedagogical educational institutions in the Republic of Uzbekistan and the trend towards reforming medical education, the introduction of medical sciences, the goal can be achieved through various games. One of the methods for forming motivation for learning are business and role-playing games that simulate reality and represent a sequence of actions that must be performed to achieve a certain result.